Conductive silk protein material and preparation method and application thereof

By modifying the original oxidation polymerization and cell derivative substrate of polypyle and syquasitic sponge, the conductive wire protein material is prepared, solving the problem that a single silk protein material cannot satisfy the conductivity and biocompatibility, and realizes the material of the material. Stable conductivity and excellent mechanical characteristics are suitable for the application of organizational engineering and flexible electronic devices.

CN116656137BActive Publication Date: 2025-01-28BEIJING UNIV OF CHINESE MEDICINE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310548961.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-16
Publication Date
2025-01-28
Estimated Expiration
2043-05-16

AI Technical Summary

Technical Problem

In the prior art, when building engineered tissues and preparing flexible electronic devices, a single silk fibroin material cannot meet the simultaneous requirements of conductivity and biocompatibility, and the near-field electrospinning technology has limitations on short circuit.

Method used

Polypyrum and filamental protein sponge are used for in situ oxidation polymerization, combined with cell derivative substrate modification, and prepared the electroconductant protein material. This material combines polypyrine conductivity and silk protein biocompatibility to form composite materials with stable conductivity and excellent mechanical characteristics.

Benefits of technology

It realizes the good biocompatibility, biodegradability, and stable conductivity of the material. It is suitable for the application of external construction and flexible electronic devices in tissue engineering, providing a platform for efficient nerve cell growth and neural network formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116656137B_ABST
    Figure CN116656137B_ABST
Patent Text Reader

Abstract

The present invention discloses a conductive silk fibroin material and a preparation method and application thereof. The preparation method comprises: (1) extraction of silk fibroin solution; (2) preparation of silk fibroin sponge; (3) in situ oxidative polymerization of polypyrrole and silk fibroin sponge; (4) modification of cell-derived matrix. The preparation process is simple and mild, and the composite material has the advantages of good biocompatibility, biodegradability, stable conductivity, excellent mechanical properties, etc., and is further combined with electrical stimulation to verify the physical and chemical properties of the composite material in the in vitro construction of engineered neural tissue. The preparation method and application described in the present invention provide new ideas for the development of new bionic materials, and provide a good three-dimensional neural tissue in vitro model for new drug development, drug screening and disease research.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tissue engineering, and in particular relates to a conductive silk protein material and a preparation method and application thereof. Background Art

[0002] Silk is a common, pure natural bio-organic material, consisting of an outer layer of sericin and an inner layer of silk fibroin, with silk fibroin (SF) accounting for about 70% to 80% of the total amount of silk fibroin. Silk fibroin has attracted great attention from researchers due to its excellent biocompatibility, unique mechanical properties, high surface mass ratio, and diverse forms. It has great potential in the field of biomedical application materials. Studies have confirmed that silk fibroin can be used as a substrate and carrier material for cell culture, in vitro tissue engineering construction, drug sustained release, clinical antibacterial dressings, surgical sutures, etc., and has achieved good results.

[0003] However, the use of a single silk protein has not yet achieved good results in the construction of engineered tissues and the preparation of flexible electronic devices. For neurite outgrowth and nerve regeneration, the use of conductive materials and electrical stimulation (ES) is a common and highly effective means. In addition, the addition of conductive materials will affect the membrane potential of neurons, while causing changes in the chemical information inside neurons and changes in related signal transduction pathways. Therefore, the composite of scaffold materials and conductive materials can effectively promote the adhesion of nerve cells, accelerate the conduction of electrical signals between neurons, and thus promote the formation of neural networks.

[0004] Compared with traditional conductive materials (metal materials, inorganic semiconductor materials, etc.), the newly developed conductive polymer materials in recent years have attracted the attention of researchers due to their superior conductivity, better biocompatibility and flexibility, and the characteristics of both polymer materials and conductive materials. Therefore, using conductive polymer materials to modify silk fibroin can not only make the composite material have unique physical and chemical properties, promote the conduction of electrical signals between neurons and the formation of neural networks, but also respond to specific external stimuli and have a certain degree of intelligence. The above advantages lay the foundation for its application in the fields of tissue engineering, sensors and flexible electronic devices.

[0005] Among many conductive polymer materials, polypyrrole (Ppy) has become a research hotspot in recent years due to its excellent biocompatibility, adjustable electrical conductivity and low cost. Methods for modifying silk fibroin using polypyrrole include different polymerization methods such as in-situ oxidative polymerization and electrochemical polymerization of silk fibroin. Sun Donghao reported a polypyrrole / silk conductive composite material prepared by on-site adsorption polymerization. The material exhibited good and stable conductivity. The fabric obtained after treatment exhibited excellent UV resistance and higher surface hydrophobicity, which can be used to manufacture antistatic work clothes or UV protection product materials (Preparation and Properties of Polypyrrole / Silk Conductive Composite Materials [J]. Silk, 2009, No. 540 (04): 13-16.). Liu Sha et al. prepared a conductive and oriented polypyrrole / silk protein scaffold through oriented electrospinning and 3D bioprinting methods, and found that hippocampal neurons showed good activity and neurite outgrowth on the scaffold (Research on "double-conducting" neural scaffold-mediated hippocampal neurons [J]. Journal of Transportation Medicine, 2019, 33(04): 332-336.).

[0006] Extracellular matrix (ECM) plays an important role in maintaining and establishing a microenvironment for tissue regeneration. Compared with decellularized scaffolds or extracellular matrix hydrogels derived from tissues or organs, extracellular matrix scaffolds derived from cultured cells have attracted the attention of researchers (The extracellular matrix as a key regulator of intracellular signalling networks[J]. Br J Pharmacol. 2019 Jan; 176(1): 82-92.). In recent years, researchers have used cell-derived extracellular matrices to modify various types of scaffold materials and used them for research on stem cell development regulation, tissue engineering construction or in vivo transplantation repair therapy. Among them, the application of Schwann cell-derived extracellular matrix-modified chitosan / silk fibroin materials to sciatic nerve gaps has shown good repair effects (Chitosan / silk fibroin-based, Schwann cell-derived extracellular matrix-modified scaffolds for bridging rat sciatic nerve gaps[J]. Biomaterials. 2014 Feb; 35(7): 2253-63.). Therefore, modification of cell-derived matrix (ECM) on conductive silk protein materials is expected to provide various soluble growth factors and extracellular matrix proteins to nerve cells, promote the adhesion of nerve cells on the scaffold, and then promote axon outgrowth and neural network formation in engineered neural tissues.

[0007] Patent 202010438109.9 discloses a method for preparing a polypyrrole / silk fibroin composite conductive tissue engineering scaffold, which describes a polypyrrole / silk fibroin composite conductive tissue engineering scaffold prepared based on a near-field electrospinning device, which has the characteristics of conductivity, biodegradability, diameter close to the extracellular matrix environment, and orderly fiber distribution. However, near-field electrospinning technology will cause short circuits in the process of preparing conductive materials, which has certain limitations. Patent 201910171992.7 discloses a composite conductive fiber and a preparation method thereof, which describes a method for preparing a polypyrrole / PBT-silk fibroin blended fiber. This method will not damage the structure and properties of the blended fiber itself, and the introduction of PBT spinning solution improves the hygroscopicity of the blended fiber. However, the patent does not contain an explanation of the performance of the composite conductive fiber and the corresponding data, pictures and other experimental results, and the description of the corresponding technical solution is not sufficient to support the material advantages described by the patent applicant. Patent 201810299533.2 discloses a conductive regenerated silk fibroin membrane and its preparation method, describing a preparation method of a silk fibroin membrane grafted with polypyrrole, and the composite material can improve the performance of the regenerated silk fibroin membrane and eliminate static electricity. However, the patent does not contain a description of the performance of the conductive regenerated silk fibroin membrane and the corresponding data, pictures and other experimental results, and the description of the corresponding technical solution is not sufficient to support the material advantages described by the patent applicant.

[0008] In summary, the preparation of composite materials with stable conductive properties, good biocompatibility and the ability to promote tissue regeneration for application in in vitro tissue engineering construction, sensors and flexible electronic devices is an urgent problem to be solved in related fields. Summary of the invention

[0009] The purpose of the present invention is to provide a conductive silk fibroin material and a preparation method and application thereof.

[0010] A conductive silk protein material is prepared by using polypyrrole and silk protein as raw materials to prepare a polypyrrole / silk protein sponge, which is then modified by a cell-derived matrix.

[0011] A method for preparing a conductive silk fibroin material is carried out according to the following steps:

[0012] (1) Extraction of silk fibroin solution: silk cocoons are used as raw materials and are prepared through the steps of degumming, dissolution, and dialysis;

[0013] (2) Preparation of silk fibroin sponge: Using 8% to 12% concentration of silk fibroin solution, a silk fibroin sponge was prepared by salting out method;

[0014] (3) In situ oxidative polymerization of polypyrrole and silk fibroin sponge: Polypyrrole was polymerized onto the silk fibroin sponge by in situ oxidative polymerization;

[0015] (4) Preparation of polypyrrole / silk fibroin sponge modified with glial cell-derived matrix: The passaged glial cells were directly inoculated on the sterilized polypyrrole / silk fibroin sponge for culture, and decellularization was performed for 7-13 days to retain the extracellular matrix.

[0016] The degumming operation steps of step (1) are as follows: add 5 g of shredded silkworm cocoon pieces into 2 L of boiling 0.02 M Na2CO3 solution, boil for 30 min with constant stirring, rinse the silk fibroin in ultrapure water for several times, take out the silk fibroin, squeeze out the water, spread it on tin foil, and dry it in a fume hood overnight.

[0017] The dissolution operation steps of step (2) are as follows: add dry silk fibroin to a 50 mL glass beaker, then add 9.3 M lithium bromide solution to the beaker, the silk fibroin fibers are completely immersed in the lithium bromide solution, and placed in a 60° C. oven to dissolve for 4 hours to prepare a silk fibroin fiber-lithium bromide solution.

[0018] The dialysis operation steps of step (1) are as follows: use a syringe to inject the silk fibroin fiber-lithium bromide solution into a dialysis bag with sealed ends, place the dialysis bag in 2L of ultrapure water, replace the ultrapure water 6 times within 48 hours, use a syringe to take out the silk fibroin solution and place it in a 50ml centrifuge tube, centrifuge at 12000rpm at 4°C for 30min to remove impurities, retain the supernatant, and prepare a silk fibroin solution.

[0019] The salting-out operation steps of step (2) are as follows: adding salt particles into the silk fibroin solution, waiting for the silk fibroin solution to dry and solidify, and obtaining a silk fibroin sponge.

[0020] The operation steps of the in situ oxidative polymerization in step (3) are as follows: weigh 70 μL of pyrrole monomer and 8 mL of 1M tannic acid solution, mix them, dilute to 20 mL with ultrapure water, immerse the silk fibroin sponge in the above solution and react for 30 minutes at room temperature; weigh 0.632 g of FeCl3·6H2O and dissolve it in 20 ml of ultrapure water, mix the ferric chloride solution, pyrrole-tannic acid solution and silk fibroin sponge, and place them at 4°C to react overnight to prepare a 50 mM polypyrrole / silk fibroin sponge.

[0021] The decellularization operation steps in step (4) are as follows: treat the cells with a decellularization reagent of 0.5% TrixonX-100 + 20 μM ammonia for 5 minutes, remove the decellularization solution, and wash three times with sterile PBS to prepare a cell-derived matrix-modified composite material.

[0022] The conductive silk protein material is used in the in vitro construction of engineered neural tissue.

[0023] Beneficial effects of the present invention: The present invention adopts an in-situ oxidative polymerization method to polymerize polypyrrole and silk fibroin sponge in situ, and the prepared conductive silk fibroin material has the advantages of good biocompatibility, biodegradability, stable conductivity, excellent mechanical properties, etc. Further, by modifying the cell-derived matrix combined with electrical stimulation, its physical and chemical properties are verified in the in vitro construction of engineered neural tissue. The preparation method and application described in the present invention provide new ideas for the development of new bionic materials, and provide a good three-dimensional neural tissue in vitro model for new drug development, drug screening and disease research. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The surface morphology of polypyrrole / silk fibroin sponge;

[0025] Scale bars: a: 300 μm; b: 15 μm.

[0026] Figure 2 To test the thermal stability of polypyrrole / silk fibroin sponge.

[0027] Figure 3 To test the conductivity of polypyrrole / silk fibroin sponge;

[0028] Where, a: voltammetric curve; b: conductivity.

[0029] Figure 4 To test the mechanical properties of polypyrrole / silk fibroin sponge;

[0030] Wherein, a: tensile curve; b: average maximum deformation; c: maximum fracture stress.

[0031] Figure 5 The effect of different concentrations of polypyrrole / silk fibroin sponge on cell activity;

[0032] Among them, a: CCK-8 was used to detect the activity of neurons cultured on different concentrations of polypyrrole / silk protein scaffolds on the 1st, 3rd and 5th days; day1: SF vs 50-Ppy / SF (*P<0.05), day5: SF vs 20-Ppy / SF (**P<0.01); b: Live / Dead staining of neurons cultured on different concentrations of polypyrrole / silk protein scaffolds on the 1st, 3rd and 5th days, scale bar = 100μm.

[0033] Figure 6 It is the installation of the electrical stimulation device and the application of electrical stimulation.

[0034] Figure 7 To detect calcium influx signals in engineered neural tissues constructed based on ECM-Ppy / SF composite materials;

[0035] Among them, a: representative CLSM images of intracellular calcium in each group of samples; b: analysis of calcium fluorescence intensity changing with time; c: statistical analysis of the average intracellular fluorescence intensity (**p<0.01). DETAILED DESCRIPTION

[0036] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0037] Example 1 Preparation and characterization of silk fibroin sponge

[0038] Extraction of silk fibroin (SF) solution: Add 5g of fully shredded silkworm cocoon pieces to a boiling 2L 0.02M Na2CO3 solution, stir and boil for 30min to remove sericin. Rinse the silk fibroin several times in ultrapure water, take out the silk fibroin, squeeze out the water, spread it on a clean tin foil, and dry it in a fume hood overnight. Add the dried silk fibroin to a 50ml glass beaker, and then add a certain volume of 9.3M lithium bromide solution (9.3M lithium bromide solution (LiBr): After the silk fibroin is dried, weigh the mass of the silk fibroin. Multiply the mass of the silk fibroin by 4 to obtain the total volume (L) of the required lithium bromide solution, and weigh the mass of the lithium bromide powder (g) = 86.85×9.3×total volume (L) of the lithium bromide solution). The silk fiber is completely immersed in the lithium bromide solution and placed in a 60℃ oven to dissolve for 4h. Use a syringe to inject the thick silk fibroin fiber-lithium bromide solution into a dialysis bag sealed at both ends, and place the dialysis bag in 2L ultrapure water. Replace the ultrapure water 6 times within 48 hours to fully replace the lithium bromide solution. Use a syringe to take out the silk fibroin solution and place it in a 50ml centrifuge tube. Centrifuge at 12000rpm for 30 minutes at 4°C to remove impurities and retain the supernatant to prepare a silk fibroin solution.

[0039] Preparation of silk fibroin sponge (SF sponge): The silk fibroin sponge was prepared by the salting-out method. The sodium chloride particles with a pore size of less than 500 μm were screened with a sieve. 4 g of sodium chloride particles were weighed, and 2 ml of 10% silk fibroin solution was added to the mold. The sodium chloride particles were slowly and evenly poured on the top of the silk fibroin solution in the mold, and tapped to remove bubbles. The mixture was placed at room temperature for 48 hours to allow the silk fibroin to gel. The material was taken out and placed in 2 L of ultrapure water to remove the sodium chloride particles, and a porous silk fibroin sponge was obtained. The scaffold was cut into a uniform cylindrical material (6 mm in diameter and 1 mm in thickness) using a punch for subsequent experiments, and stored in ultrapure water at 4 °C.

[0040] Characterization of Silk Fibroin Sponge: Figure 1The results of scanning electron microscopy showed that the surface of silk fibroin sponge was smooth, and the pore distribution and pore size were relatively uniform; Figure 2 Thermogravimetric analysis results show that the silk fibroin sponge shows the first weight loss at temperatures below 100°C due to the water contained in it; Figure 3 The results showed that the silk fibroin sponge had no electrical conductivity; Figure 4 The results of mechanical properties test showed that the average maximum deformation of silk fibroin sponge was (69.5±6.2)%, the breaking stress was (47.3±2) kPa.

[0041] Example 2 Preparation of 10 mM polypyrrole / silk fibroin sponge

[0042] Weigh 14 μL of pyrrole monomer and 1.6 mL of 1M tannic acid solution, mix well, dilute to 20 mL with ultrapure water, immerse the silk fibroin sponge in the above solution and react at room temperature for 30 min. Weigh 0.126 g of FeCl3·6H2O and dissolve it in 20 ml of ultrapure water, mix well, mix the ferric chloride solution, pyrrole-tannic acid solution and silk fibroin sponge, and react at 4°C overnight to prepare a 10 mM polypyrrole / silk fibroin sponge.

[0043] Example 3 Preparation of 50 mM polypyrrole / silk fibroin sponge

[0044] Weigh 70 μL of pyrrole monomer and 8 mL of 1M tannic acid solution, mix well, dilute to 20 mL with ultrapure water, immerse the silk fibroin sponge in the above solution and react at room temperature for 30 minutes. Weigh 0.632 g of FeCl3·6H2O and dissolve it in 20 ml of ultrapure water, mix well, mix the ferric chloride solution, pyrrole-tannic acid solution and silk fibroin sponge, and react at 4°C overnight to prepare a 50 mM polypyrrole / silk fibroin sponge.

[0045] Example 4 Characterization of polypyrrole / silk fibroin sponge (Ppy / SF)

[0046] The surface morphology of pure silk fibroin sponge and polypyrrole / silk fibroin sponge with different concentrations was observed by scanning electron microscopy. Figure 1 ab are scanning electron micrographs of polypyrrole / silk fibroin sponges prepared at pyrrole concentrations of 0mM, 5mM, 10mM, 20mM, and 50mM, respectively. The results show that after in situ polymerization of polypyrrole, the pore size and distribution of the scaffold did not change significantly, and the pore distribution was uniform. In addition, after the silk fibroin sponge polymerized polypyrrole, polypyrrole particles and aggregates were formed on the surface of the scaffold, and the morphology changed from smooth to rough. The higher the pyrrole concentration, the rougher the surface. This rough material surface is more conducive to cell adhesion. Figure 1The results of scanning electron microscopy showed that both 10mM and 50mM polypyrrole / silk fibroin sponge scaffolds showed relatively uniform pore distribution and pore size. Compared with 10mM Ppy / SF, the surface of 50mM Ppy / SF was rougher, and more polypyrrole particles and aggregates were visible.

[0047] Figure 2 The results of thermogravimetric analysis showed that polypyrrole / silk fibroin sponges with different concentrations exhibited similar thermal degradation behaviors. They all showed the first weight loss below 100°C, corresponding to the water contained in the silk fibroin fiber itself. The water content of polypyrrole / silk fibroin sponges with different concentrations was comparable, indicating that the water retention properties of the silk fibroin sponge did not change after the polymerization of polypyrrole. Subsequently, the temperature continued to rise, and the composite material began to degrade after 300°C, with continuous weight loss. Due to the compounding of polypyrrole, the thermal stability of the scaffold was slightly improved but not obvious; 10mM Ppy / SF and 50mM Ppy / SF showed similar thermal degradation behaviors, both showing the first weight loss below 100°C, both starting to degrade after 300°C, and continuous weight loss.

[0048] In order to explore the conductivity of the composite material, the conductivity of the composite material was evaluated using a three-electrode electrochemical workstation. The voltammetric cycle curve shows that with the increase of pyrrole concentration, the envelope area increases and the ability of the composite material to store charge increases ( Figure 3 a), and then the impedance of the composite material was detected and the conductivity was calculated according to the formula ( Figure 3 b), The conductivity results of polypyrrole / silk fibroin sponges with different concentrations show that with the increase of pyrrole concentration, the conductivity of polypyrrole / silk fibroin sponges also increases, which is significantly different from the conductivity of pure silk fibroin sponges. Figure 3 The results show that compared with 10mM Ppy / SF, 50mM Ppy / SF has a larger envelope area, a stronger ability to store charge, and a higher conductivity.

[0049] It is unwise to simply pursue the conductivity of the material. A good scaffold material must also have appropriate mechanical properties to create a mechanical microenvironment suitable for cell growth. Therefore, a tensile test was conducted on the polypyrrole / silk fibroin sponge ( Figure 4). The results showed that when the pyrrole concentration gradually increased, the average maximum deformation of the prepared scaffold material gradually decreased, from the maximum deformation of the pure silk fibroin sponge (69.5±6.2)% to the maximum deformation of the 50mM polypyrrole / silk fibroin sponge (25.1±2)%. With the increase of pyrrole concentration, the fracture stress that the polypyrrole / silk fibroin sponge can withstand first increased and then decreased. The fracture stress increased from the original (47.3±2) kPa of the pure silk fibroin sponge to (66.1±1.6) kPa of the 10mM polypyrrole / silk fibroin sponge, and then gradually decreased to (45.3±4) kPa of the 50mM polypyrrole / silk fibroin sponge. The results show that the addition of polypyrrole will significantly change the mechanical properties of the original silk fibroin sponge. The higher the polypyrrole concentration, the easier it is for the polypyrrole / silk fibroin sponge to break. Combining the two results for comprehensive analysis, in order to retain the tensile strength of the material to the greatest extent, polypyrrole / silk fibroin sponge with pyrrole concentrations of 5mM and 10mM is more conducive to providing a suitable mechanical microenvironment for cells and is more suitable as a tissue engineering scaffold material.

[0050] The polypyrrole / silk composite material was sterilized with 75% ethanol solution, soaked overnight and then irradiated with ultraviolet light for 30 minutes, washed three times with sterile PBS solution, and the scaffold was balanced with culture medium before inoculating cells. The isolated primary cortical neurons were inoculated at the same density on 5mM, 10mM, 20mM and 50mM polypyrrole / silk scaffolds, and the activity of neurons on polypyrrole / silk scaffolds of different concentrations was detected by CCK-8 staining on day 1, day 3 and day 5, respectively. The live / dead staining was used to detect the live and dead status of neurons on polypyrrole / silk scaffolds of different concentrations, and then a polypyrrole concentration that was most suitable for the survival of neurons was selected, and only the optimal concentration of polypyrrole / silk scaffold was used for subsequent experiments.

[0051] Figure 5 The results of CCK-8 detection showed that the OD value of nerve cells increased with the extension of culture time. At the same time, with the increase of polypyrrole concentration, the activity of nerve cells weakened, especially on the first and third days of in vitro culture. Live / Dead staining results showed that with the increase of polypyrrole concentration, the number of dead cells of nerve cells gradually increased, and the number of dead cells increased significantly at 50mM Ppy / SF. The combination of CCK-8 detection and Live / Dead staining suggested that the activity of neurons was best at 10mM Ppy / SF.

[0052] Based on the above results, it is most appropriate to select 10mM polypyrrole / silk fibroin sponge for the subsequent in vitro construction of engineered neural tissue, which maximizes the conductivity of the composite material and provides the best mechanical properties and biocompatibility for the subsequent growth of neurons.

[0053] Example 5 Preparation of polypyrrole / silk fibroin sponge modified with glial cell-derived matrix

[0054] The brain tissue of newborn SD rats was obtained, the cerebral cortex was separated, the meninges were removed and cut into pieces, and digested with 0.05% trypsin for 30 minutes, then the digestion was stopped with serum-containing medium, and the fibroblasts were removed by differential attachment for 1 hour. Then, the mixed glial cells were cultured with DMEM+10% FBS medium, and ascorbic acid was added to promote the large-scale secretion of extracellular matrix. The glial cells after passage were directly inoculated on the sterilized polypyrrole / silk fibroin sponge for culture, and decellularization was performed after 10 days to retain the extracellular matrix. The overall method of removing glial cells and retaining extracellular matrix is ​​briefly described as follows: the cells were treated with a decellularization reagent of 0.5% TrixonX-100+20μM ammonia for 5 minutes, and then the decellularization solution was removed and washed 3 times with sterile PBS to prepare a cell-derived matrix-modified composite material, which was stored in cell culture medium at 4°C and used within 1 week.

[0055] In vitro construction and characterization of engineered neural tissue based on ECM-Ppy / SF composite materials: Isolation of primary rat cortical neurons, inoculation on ECM-Ppy / SF composite materials for culture, construction of in vitro engineered neural tissue: 18-day pregnant SD rats were used, and after being killed by cervical dislocation, they were immersed in 75% ethanol for disinfection for 5 minutes. The embryos were removed and placed in ice PBS solution, the brain was separated, and the cerebral cortex was peeled off and the meninges and blood vessels were removed under a stereomicroscope using ophthalmic forceps. Use scissors to cut the tissue as finely as possible, add a certain volume of 0.05% trypsin and place it in a CO2 incubator for digestion for 30 minutes. During digestion, the tissue was patted every 5 minutes to prevent aggregation from affecting the digestion effect. Trypsin inhibitor was used to stop digestion, and the suspension was blown into a single cell suspension with a pipette. Use 200 mesh and 100 mesh filters to filter out undigested cells and tissues, centrifuge at 1000rpm for 5 minutes, discard the supernatant and resuspend the cells with neuronal culture medium, and use 5×10 6 The cells were seeded at a density of 10 cells / scaffold on the ECM-Ppy / SF composite material, and the medium was replaced by half every other day.

[0056] Mounting of electrical stimulation device, application of electrical stimulation ( Figure 6 ) and calcium signaling in engineered neural tissues ( Figure 7 ): During the culture of engineered neural tissue, the samples in the electrical stimulation group were subjected to electrical stimulation for 2 h every other day, with a voltage of 100 mV and a frequency of 50 Hz. The electrical stimulation device was self-assembled and built ( Figure 6Calcium imaging was used to perform functional imaging of neurons and neural networks in engineered neural tissues constructed on ECM-Ppy / SF composite materials. On the 14th day of in vitro culture of engineered neural tissues, samples were collected and Ca 2+ Sensitive indicator Fluo-4 AM to measure cellular Ca in engineered neural tissues 2+ Concentration. First, wash with PBS three times to remove residual culture medium, incubate with 2μM Fluo-4 dye at 37°C for 30min, then wash with calcium imaging buffer and incubate in buffer for 20min before imaging. The sample was placed on a coverslip and imaged at room temperature using a live cell workstation to collect and quantify fluorescence excitation images ( Figure 7 ).

[0057] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a conductive silk fibroin material, characterized in that: Follow these steps: (1) Extraction of silk fibroin solution: silk cocoons are used as raw materials and are prepared through the steps of degumming, dissolution, and dialysis; (2) Preparation of silk fibroin sponge: Using 8% to 12% concentration of silk fibroin solution, silk fibroin sponge was prepared by salting out method; (3) In situ oxidative polymerization of polypyrrole and silk fibroin sponge: Polypyrrole was polymerized onto the silk fibroin sponge by in situ oxidative polymerization; (4) Preparation of polypyrrole / silk fibroin sponge modified with glial cell-derived matrix: The passaged glial cells were directly inoculated on the sterilized polypyrrole / silk fibroin sponge for culture, and decellularization was performed after 7-13 days to retain the extracellular matrix; The glial cells were obtained by taking brain tissue of newborn SD rats, separating the cerebral cortex, removing the meninges and cutting into pieces, digesting with 0.05% trypsin for 30 minutes, then stopping the digestion with a serum-containing culture medium, and removing fibroblasts by differential attachment for 1 hour, then culturing the mixed glial cells with a DMEM+10% FBS culture medium, and adding ascorbic acid to promote the secretion of a large amount of extracellular matrix; The decellularization operation steps are as follows: treating the cells with a decellularization reagent of 0.5% TrixonX-100 + 20 μM ammonia water for 5 minutes, then removing the decellularization solution, and washing with sterile PBS for 3 times to prepare a cell-derived matrix-modified composite material.

2. The method for preparing the conductive silk fibroin material according to claim 1, characterized in that: The degumming operation steps of step (1) are as follows: add 5 g of shredded silkworm cocoon pieces into 2 L of boiling 0.02 M Na2CO3 solution, boil for 30 min with constant stirring, rinse the silk fibroin in ultrapure water for several times, take out the silk fibroin, squeeze out the water, spread it on tin foil, and dry it in a fume hood overnight.

3. The method for preparing the conductive silk fibroin material according to claim 1, characterized in that: The dissolution operation steps of step (2) are as follows: add dry silk fibroin into a 50 mL glass beaker, then add 9.3 M lithium bromide solution into the beaker, the silk fibroin fibers are completely immersed in the lithium bromide solution, and placed in a 60° C. oven to dissolve for 4 hours to prepare a silk fibroin fiber-lithium bromide solution.

4. The method for preparing the conductive silk fibroin material according to claim 1, characterized in that: The dialysis operation steps of step (1) are as follows: use a syringe to inject the silk fibroin fiber-lithium bromide solution into a dialysis bag with sealed ends, place the dialysis bag in 2L ultrapure water, replace the ultrapure water 6 times within 48 hours, use a syringe to take out the silk fibroin solution and place it in a 50ml centrifuge tube, centrifuge at 12000rpm at 4°C for 30min to remove impurities, retain the supernatant, and prepare a silk fibroin solution.

5. The method for preparing the conductive silk fibroin material according to claim 1, characterized in that: The salting-out operation steps of step (2) are as follows: adding salt particles into the silk fibroin solution, waiting for the silk fibroin solution to dry and solidify, and obtaining a silk fibroin sponge.

6. The method for preparing the conductive silk fibroin material according to claim 1, characterized in that: The operation steps of the in situ oxidative polymerization in step (3) are as follows: weigh 70 μL of pyrrole monomer and 8 mL of 1 M tannic acid solution, mix them evenly, dilute to 20 mL with ultrapure water, immerse the silk fibroin sponge in the above solution and react for 30 min at room temperature; weigh 0.632 g of FeCl3·6H2O and dissolve it in 20 ml of ultrapure water, mix the ferric chloride solution, pyrrole-tannic acid solution and silk fibroin sponge, and place them at 4°C to react overnight to prepare a 50 mM polypyrrole / silk fibroin sponge.

7. Use of the conductive silk protein material according to claim 1 in the in vitro construction of engineered neural tissue.

Citation Information

Patent Citations

  • Electrically-conductive regenerated silk fibroin film and preparation method thereof

    CN108467508A

  • Composite conductive fiber and preparation method thereof

    CN109853240A

  • Preparation method of polypyrrole / silk fibroin composite conductive tissue engineering scaffold

    CN111671973A